The determinants of foreign trading volume of stocks listed in multiple markets - Dodd, Olga; Louca, Christodoulos; Paudyal, Krishna (My University, 2015)
We examine the determinants of the foreign trading volume of European stocks listed in multiple markets. The results suggest that stocks that cross-list in foreign markets that are larger and more liquid than their home markets, and stocks for which foreign investors acquire information at a lower cost, experience higher volumes of trade in foreign markets. Stocks that are cross-listed in the US are more attractive to foreign traders than those cross-listed in European markets. Differences in motives to trade in American vs. European markets are also uncovered. Among the fundamental motives to trade, diversification benefit and stock risk are more important for investors trading in American markets while the difference in trading costs is more vital for investors in European markets. Among the informational motives to trade, the firm's presence in foreign product markets and the foreign information factor are significant determinants of trading in American markets but not in European markets.
Keywords: Cross-listing; Foreign trading volume; Information environment; Location of equity trading; Market liquidity; Multiple market trading; Stock exchange competition